Correlation of Immature Granulocytes and C-Reactive Protein with Blood Culture in Neonatal-SIRS at Gambiran Hospital - Muthia Maraya Hasna; Sri Widyaningsih; M. Reza Utama; Gina Noor Djalilah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Sepsis can occur in patients with Systemic Inflammatory Response Syndrome (SIRS) symptoms, especially in neonates due to their underdeveloped immune systems. Blood culture as the gold standard test to diagnose sepsis in SIRS patients takes a long time to perform. The other rapid test parameters are needed to support the early diagnosis of infection (sepsis) in SIRS patients, including Immature Granulocytes (IG%) and C-Reactive Protein (CRP). This study aimed to determine the correlation between IG% with blood culture and CRP with blood culture in neonatal SIRS patients at Gambiran Hospital, Kediri. The research design used retrospectively using secondary data. A total of 63 samples were obtained using simple random sampling on the medical record of neonatal SIRS patients who met the inclusion criteria, without any exclusion criteria. There were significant results with a value of p=0.000 (p < 0.05) between IG% and blood culture using the Mann-Whitney test, as well as on CRP and blood culture using the independent samples T-test. The bivariate statistical test between IG% and CRP was carried out using the Spearman test and showed significant results with p=0.000 (p < 0.05) with a correlation coefficient (rs) of 0.740, which indicated a strong positive relationship. It was concluded that there was a correlation between IG% and CRP with blood culture in neonatal SIRS patients.